Genome Sequencing of Pantoea agglomerans strain NC, isolated from peanut bacterial wilt nursery. (October 2019) - Wang, X Z; Tang, Y Y; Wang, Z W; Wu, C Z; Chen, J H; Wu, Q; Wang, C T
Abstract: Pantoea agglomerans was ubiquitous in nature and it has been identified as an effective microbial antagonist against fungal pathogens associated with several plants. Here, we report the draft genome sequence of P. agglomerans strain NC which was isolated from bacterial wilt infected peanut (Arachis hypogaea) in Nan Chang city of China.